Seborrheic Dermatitis Treatment Using a Standardized Medical Insurance-Approved Korean Medicine: a case report - Yeonkyoung Pak; Sangwon Shin (Korean Pharmacopuncture Institute, 2024)
Background: Conventional treatments for seborrheic dermatitis often lead to a recurring cycle of symptom improvement and worsening, resulting in chronic conditions. Thus, safer and more effective alternatives are needed. In Korean medicine, Hwangryunhaedok-tang tablets, targeted at treating the fire-heat syndrome, offer a more fundamental approach to manage seborrheic dermatitis.Clinical Features and Outcomes: In this study, we monitored the changes in the symptoms of two patients with seborrheic dermatitis who were treated with Hwangryunhaedoktang tablets. The patients were administered this medication during the treatment period. The effectiveness of the treatment was assessed by visually recording changes in the affected skin areas using photographs and evaluating symptoms such as heat, itching, and stinging in these areas using a visual analog scale (VAS). Visible improvements in the patients' skin conditions were observed after taking Hwangryunhaedok-tang tablets. Following treatment, VAS scores for subjective symptoms such as heat sensation, itching, and stinging in the affected areas decreased.Conclusion: This study offers evidence of a potential alternative approach for treating seborrheic dermatitis using Kyungbang Hwangryunhaedok-tang tablets. However, it highlights the necessity for further research on the appropriate dosage, side effects, and long-term effectiveness of this treatment.